Shield key: a deep learning process for the generation of public & private keys using hybrid architecture in blockchain - Joy, Tanvir Ahmed; Ahmed, Sultan Gias Uddin; Ahmed, Mir Abrar; Islam, Sazzad UL; Nima, Menuka Tasnim (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.